Urban streetscape: activating the public realm and increasing safety through multifunctional user-oriented spaces - Whitford, Katherine A. (Kansas State University, 2013)
Colorado Springs' downtown streets are primarily automobile-oriented, which has lead to a deficiency of multi-modal transportation networks and user-oriented environments. The streets lack engaging public space, pedestrian and bicyclist amenities, native landscaping, and stormwater management systems. The auto-centric design presents significant physical and perceived safety issues concerning pedestrians and bicyclists in the right-of-way. The aim of this study is to redesign the downtown core of Colorado Springs to foster multifunctional user-oriented spaces which enhance overall environmental, social, and economic benefits. In order to complete this study, background literature research and a series of case studies were conducted. The ultimate goal of this masters project is to create a retrofit streetscape design for Colorado Springs that can be used as a model for other planners and designers. The results of this project will be significant to designers because it will provide them with information regarding the best practices for designing urban streetscapes that activate the public realm and promotes safety.
Keywords: Urban streetscape; Colorado Springs; Green infrastructure; Landscape Architecture (0390)